Learning and Teaching Mathematics. Weaving the Nexus of Values, Attitudes and Beliefs : Selected Works of Dr Tasos Barkatsas - Barkatsas, Tasos (Educational Research E-Books Online, Collection 2026., 2025)
This collection represents two decades of dedicated and rigorous empirical research spanning across multiple dimensions of mathematics education. Through a theoretical approach that highlights the significance of analytical depth in the research process, the studies included in this book explore significant themes in Mathematics Education that span across mathematics learning, student attitudes toward mathematics, beliefs, engagement, values, motivation, gender differences, technology integration and effective pedagogical strategies over the past two decades. The scope of this work makes a substantial contribution to the ongoing discourse on best practices in mathematics teaching, equity in mathematics education and the evolving and significant role of inclusive mathematics education in the 21st century and beyond. One of the key strengths of this collection can be found in its simultaneous focus on local and global perspectives.